Only option d is the correct answer as x = 3 is a solution to the equation.
To solve this problem, we have to substitute the value of x into the equation and see if it is equal to zero.
<h3>Solution of an Equation</h3>
a)
![3x+7 = x - 8](https://tex.z-dn.net/?f=3x%2B7%20%3D%20x%20-%208)
when x = -6
substitute the value of x
![3x+ 7 = x - 8\\x = -6\\3x-x = -8-7\\2x = -15\\2(-6) = -15\\-12 \neq -15](https://tex.z-dn.net/?f=3x%2B%207%20%3D%20x%20-%208%5C%5Cx%20%3D%20-6%5C%5C3x-x%20%3D%20-8-7%5C%5C2x%20%3D%20-15%5C%5C2%28-6%29%20%3D%20-15%5C%5C-12%20%5Cneq%20-15)
equation (a) is wrong.
b)
![-2x-8=-4x-1\\x = 3](https://tex.z-dn.net/?f=-2x-8%3D-4x-1%5C%5Cx%20%3D%203)
collect like terms and substitute for x
![-2x-8=-4x-1\\x = 3\\-2x+4x= -1+8\\2x = 7\\2(3) = 7\\6\neq 7](https://tex.z-dn.net/?f=-2x-8%3D-4x-1%5C%5Cx%20%3D%203%5C%5C-2x%2B4x%3D%20-1%2B8%5C%5C2x%20%3D%207%5C%5C2%283%29%20%3D%207%5C%5C6%5Cneq%207)
equation(b) is wrong
c)
![-5x+7 = 2x - 14\\x = -8\\](https://tex.z-dn.net/?f=-5x%2B7%20%3D%202x%20-%2014%5C%5Cx%20%3D%20-8%5C%5C)
collect like terms and substitute for x
![-5x+7 = 2x - 14\\x = -8\\7+ 14 = 2x + 5x\\21 = 7x\\21 = 7(-8)\\21 \neq -42](https://tex.z-dn.net/?f=-5x%2B7%20%3D%202x%20-%2014%5C%5Cx%20%3D%20-8%5C%5C7%2B%2014%20%3D%202x%20%2B%205x%5C%5C21%20%3D%207x%5C%5C21%20%3D%207%28-8%29%5C%5C21%20%5Cneq%20-42)
d)
![-(x-1)=4x-5-3x\\x = 3\\-(x-1) = 4x -5 -3x\\-x+1 = x- 5\\2x = 6\\2(3) = 6\\6 = 6\\](https://tex.z-dn.net/?f=-%28x-1%29%3D4x-5-3x%5C%5Cx%20%3D%203%5C%5C-%28x-1%29%20%3D%204x%20-5%20-3x%5C%5C-x%2B1%20%3D%20x-%205%5C%5C2x%20%3D%206%5C%5C2%283%29%20%3D%206%5C%5C6%20%3D%206%5C%5C)
From the above calculation, only option d is the correct answer as x = 3 is a solution to the equation.
Learn more on solutions of equation here;
brainly.com/question/16863577